The evaluation of the flow re-direction endoluminal device (FRED) for the treatment of selected intracranial aneurysms: a Polish multicenter study - Maciej Jaworski; Remigiusz Krysiak; Jarosław Żyłkowski; Mariusz Banach; Miłosz Zbroszczyk; Kamila Smulska; Sławomir Bereza; Katarzyna Lubkowska; Ewa Horoch-Łyszczarek; Paweł Brzegowy; Tadeusz Popiela; Wojciech Poncyljusz; et al. (Scientific Reports)
Abstract This Polish multicenter study aims to evaluate the effectiveness and safety of the Flow Direction Endoluminal Device (FRED) in treating selected unruptured intracranial aneurysms. The FRED Poland Study was an observational, multicenter, prospective study conducted in 8 Polish investigational sites. Imaging results were independently assessed by a Corelab and adverse events were adjudicated by a Clinical Events Committee (CEC). Clinical results up to 24 months and anatomical results at 6-, 12- and 24-months post-treatment were reported. A total of 86 patients with 89 target aneurysms were enrolled between January 2016 and September 2017. Most aneurysms were located on the anterior circulation (93.2%, 83/89 aneurysms) with the majority (64.0%, 57/89) being small (< 10 mm) in size. Treatment was successfully performed in 86 out of 89 cases (96.6%). The permanent neurological morbidity rate was 3.6%, and the neurological mortality rate was 2.4%. Imaging follow-up at 6 months showed complete occlusion of the aneurysm in 64.9% of cases, increasing to 79.5% at 12 months and 85.5% at 24 months. This study offers a comprehensive overview of the flow diversion treatment approach, demonstrating that the FRED device is effective and safe for use in intracranial aneurysm treatment. These results align with existing literature, reaffirming the device reliability and suitability for clinical use.